Analisis Ukuran Perusahaan Dan Corporate Governance Terhadap Manajemen Laba Di Bursa Efek Indonesia - Reni Kusuma Wardhani; Dian Efriyenti (Prosiding, 2022)
The low level of good corporate governance control in a company will increase earnings management behavior which causes problems and causes losses to the company. Population taken from on the Indonesia Stock Exchange in the 2016-2021. Samples that meet the criteria are 8 data. Based on the results of the t test Firm Size (SIZE) a significant value of 0.003 < 0.05 and a t-count value of -3.134 < -2.028 partially firm size (SIZE) has a negative and significant effect on earnings management. In managerial ownership (KM) the significant value is 0.481 > 0.05 and the t value -0.711 > -2.028 partially managerial ownership (KM) has a negative but not significant effect on earnings management. Then for institutional ownership (KI) significant value 0.924 > 0.05 and t value -0.096 > -2.028 partially institutional ownership (KI) has a negative but not significant effect on earnings management, and simultaneously or f test: firm size (SIZE), managerial ownership (KM) and institutional ownership (KI) have a significant effect on earnings management (DA) with a significance value of 0.001 < 0.05 and the result of f arithmetic is 7.310 > 2.87.